Draft genome sequence of Agrobacterium deltaense strain CNPSo 3391, isolated from a soybean nodule in Mozambique - Scherer, A.J.; Delamuta, J.R.M.; Ribeiro, R.A.; Chibeba, A.M.; Kyei-Boahen, S.; Nogueira, M.A.; Hungria, M. (American Society for Microbiology, 2019)
Agrobacterium deltaense strain CNPSo 3391 was isolated from a soybean nodule in Mozambique. Its genome size was estimated at 4,926,588 bp. This isolate carries several coding sequences for stress tolerance, but no identifiable nodulation or virulence genes. Possible ecological roles of bacteria isolated from legume nodules and closely related to Agrobacterium are discussed.